1986
DOI: 10.1063/1.336948
|View full text |Cite
|
Sign up to set email alerts
|

A photoluminescence and Hall-effect study of GaSb grown by molecular-beam epitaxy

Abstract: Unintentionally doped gallium antimonide has been grown by molecular-beam epitaxy on gallium arsenide and gallium antimonide. Substrate temperatures in the range 480 to 620 °C and antimony to gallium flux ratios from 0.65 : 1 to 6.5 : 1 have been investigated. The deposition conditions have been related to growth morphology and to the electrical and optical properties of the epitaxial films. A strong correlation has been found between the quality of the layers and the degree of excess antimony flux; the best m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(53 citation statements)
references
References 13 publications
3
49
0
1
Order By: Relevance
“…Ivanov et al 20 and Johnson et al 21 are representative of what has been reported for epitaxial GaSb on semi-insulating GaAs substrates. Ivanov et al reported 77 K hole concentrations and mobilities of 1.1x10 16 to 1.5x10 16 cm −3 and 2700 to 4580 cm 2 /Vs while Johnson et al reported 1.5x10 15 to 8x10 15 cm −3 and 756 to 310 cm 2 /Vs at that temperature, to which our values in Table II, 1x10 15 to 2x10 16 cm −3 and 3000 to 7000 cm 2 /Vs, compare favorably.…”
Section: Aip Advances 5 097219 (2015)supporting
confidence: 45%
See 2 more Smart Citations
“…Ivanov et al 20 and Johnson et al 21 are representative of what has been reported for epitaxial GaSb on semi-insulating GaAs substrates. Ivanov et al reported 77 K hole concentrations and mobilities of 1.1x10 16 to 1.5x10 16 cm −3 and 2700 to 4580 cm 2 /Vs while Johnson et al reported 1.5x10 15 to 8x10 15 cm −3 and 756 to 310 cm 2 /Vs at that temperature, to which our values in Table II, 1x10 15 to 2x10 16 cm −3 and 3000 to 7000 cm 2 /Vs, compare favorably.…”
Section: Aip Advances 5 097219 (2015)supporting
confidence: 45%
“…2 are in areal units (cm −2 ) because that is the output of the multicarrier analysis. Converting the 300 K concentrations to volumetric units we get 1.23x10 16 cm −3 for the G band and 6.28x10 16 cm −3 for the L band. The total free electron concentration is the sum of these two concentrations, 7.51x10 16 cm −3 .…”
Section: Aip Advances 5 097219 (2015)mentioning
confidence: 99%
See 1 more Smart Citation
“…GaAs (001) is a relatively usual substrate to grow high crystal quality blanket GaSb films by MBE [22][23][24]. Under appropriate growth conditions, the strain energy associated with the 7.8% lattice mismatch is relaxed through the formation of a periodic array of 90° Lomer misfit dislocations at the GaSb/GaAs [001] interface, which largely hinders the formation of threading dislocations.…”
Section: Methodsmentioning
confidence: 99%
“…Y. Li et al [18] reported on 1.63×10 16 cm -3 room temperature hole concentration at growth temperature of 490°C, while M. Lee et al [25] had 7.8×10 15 cm -3 at growth temperature 550°C. A growth rate of 1 μm/h was used by the two previous groups.…”
Section: Resultsmentioning
confidence: 99%